Vitiligo patients show significant up-regulation of aryl hydrocarbon receptor transcription factor - Farinaze Behfarjam; Zohreh Jadali (Sociedade Brasileira de Dermatologia, 2018)
Abstract: IL-22 has been implicated in the pathogenesis of vitiligo. However, the role of aryl hydrocarbon receptor transcription factor that acts as a master regulator of IL-22-producing Th22 cells is not fully understood. The goal of this study was to investigate the expression pattern of aryl hydrocarbon receptor in peripheral blood mononuclear cells of patients with vitiligo and in normal controls. Transcript levels were determined by a reverse transcription quantitative real-time polymerase chain reaction. Aryl hydrocarbon receptor mRNA expression was drastically increased in patients with vitiligo compared to healthy controls (P = 0.000). Th22 cells may contribute to abnormal immune responses underlying vitiligo.